ISLAMIC LAW BASE ON IMAM ABU HANIFAH'S VIEWS ON THE MECHANISM OF MARRIAGE FOR MUTE PEOPLE - Fitra Liana Suri; Khoirul Abror; Efa Rodiah Nur (Law Faculty of Universitas Bandar Lampung, 2022)
Marriage is an integral part of Islamic law that is inseparable from the dimensions of Islamic faith and morals. So Islam provides guidelines so that judges and courts do not deviate or deviate. Because Islamic law as a living law in the Indonesian national legal order, of course it must be able to balance and answer the problems and legal developments that occur in society. The occurrence of a marriage bond does not only have an impact on civil relations, such as the rights and obligations of husband and wife, guardianship, children's position, joint property, inheritance, kinship, neighbourhood and customs, but also involves the obligation to obey religious orders and prohibitions, both in human relations with God and human relations with humans (mu'amalah) in social life so that they are safe in this world and safe in the hereafter. The process of the marriage contract by pronouncing the consent and qabul was carried out orally. If the parties are unable to perform the consent and qabul verbally due to certain obstacles, then the marriage contract can be carried out using a sign. This research belongs to the type of library research, namely research that uses literature, both in the form of Islamic law books (fiqh books, compilations of Islamic law) related to this research. Based on the results of this study, Imam Abu Hanifah distinguishes between people who are mute since birth and normal people who become mute. If a person has the possibility to speak, then he should not use sign language because he is not classified as a mute person. However, if a person is confirmed to be mute until he dies, then the law is the same as for a mute person.